THE INFLUENCE OF LEADERSHIP STYLE AND PERFORMANCE MONITORING LECTURER OF WEST SUMATRA POLTEKPEL WITH THE WORKING CLIMATE AS INTERVENING VARIABLES - Ardian, Dede (Jurnal Cakrawala Bahari, 2025)
This study aims to determine and analyze pinfluence of leadership style on employee work climate, influence of supervision on work climate, influence of leadership style on employee performance, influence of supervision on employee performance, influence of work climate on employee performance, influence of leadership style on performance with work climate as an intervening variable and influence of supervision on performance with work climate as an intervening variable. The sample in this study were 90 lecturers at Shipping Polytechnic of West Sumatra. The sampling technique is a census technique because the number of employees is only 90 people who fill out the questionnaire. The type of data used is primary data, the data collection method uses a questionnaire with a Likert scale. Test the research instrument for validity and reliability. The data analysis technique consists of data description test, classical assumption test, path analysis and hypothesis testing. The research results found that leadership style has a positive and significant effect on the work climate of employees, phe insight has a positive and significant effect on working climate employees, model of leadership has a positive and significant effect on employee performance, supervision has a positive and significant effect on employee performance, the work climate has a positive and significant effect on employee performance, work climate does not play a role as an intervening variable between leadership style and employee performance and work climate does not play a role as an intervening variable between supervision and employee performance. This study provides suggestions that to improve employee performance, it is necessary a constructive leadership style, a more conducive working climate and increased supervision.